Effect of of torrefied wood biomass under oxidizing environment in a downdraft gasification process (2017)
ABSTRACT: The effect of composition and heating value of torrefied biomass under an oxidizing atmosphere at different conditions (180, 210, and 240 °C during 30, 75, and 120 minutes) was studied relative to downdraft gasification performance. An extended model for gasification in thermochemical equilibrium was used to evaluate the effect of pretreated biomasses, fuel-to-air equivalence ratio, and char byproduct production on the producer gas composition, reaction temperature, cold gas efficiency (CGE), and the engine fuel quality (EFQ). The model was validated with experimental data, reaching a global relative error of 8.5%. For raw or torrefied biomasses, with regard to char production, the CGE decreases if char increases; this is due to the fact that the process tends to combustion regimes when a lower amount of carbon is involved in the gasification reaction. Otherwise, the CGE and EFQ increase (up to 80% and 2.5 MJ/kg, respectively) if fuel-to-air ratio increases. With regard to the torrefied biomass, it is highlighted that CGE and EFQ increase from 77% to 82% and from 2.2 MJ/kg to 2.5 MJ/kg, respectively, when the torrefaction conditions (temperature and/or time) increase. This behavior is related to the increase of the autothermal zones in the gasification process and due to the higher heating value of torrefied biomass.